SIMULASI LAJU PENURUNAN GLUKOSA DARAH DIABETES TIPE 1 SETELAH MELAKUKAN AKTIVITAS FISIK - Muhammad Khalid (Jurnal Biofisika, 2014)
Decline rate modeling of blood glucose in type 1 diabetes after exercise that made by Roy2 not attach consumption glucose factor. In the fact, type 1 diabetes mellitus (T1DM) consume the glucose before exercise. Consumption of glucose can from food or drinks. In the research, we modify Roy’s2 model by attached glucose consumption. Result of modification model isn’t too different to experiment data. This is evident from R2 value obtained for 99.30%. In addition, this modification result isn’t much different with Anirban Roy’s model that have R2 value is 99.25%. Parameter values used for this model modification it’s identic, they are insulin injection (u1) is 15 µU min-1, exercise duration is 60 minute, patient boddy mass is 80 kg, and glucose consumption (D) is around to 10 mg min-1 dl-1 (for parameter values in modification model). Hypoglycemia will occur if amount of insulin injected into patient too much, while hyperglycemia can occur if amount of insulin injected into patient too little.